Colorimetric detection of individual biothiols by tailor made reactions with silver nanoprisms - Pei Li (Nature Portfolio, 2021)
Abstract We herein described a rapid, sensitive, and selective colorimetric sensing platform for biothiols in human serum, which relies on the dual functions of biothiols as anti-etching and aggregating agent for silver nanoprisms (AgNPRs). In principle, the target biothiols that bind to the surface of AgNPRs through Ag–S covalent interactions protect the AgNPRs from being etched by chloride ion (Cl−) in human serum, thus exhibiting the blue/purple color that is indicative of AgNPRs. On the other hand, the color of AgNPRs turned to yellow in the absence of biothiols or the presence of non-sulfur-containing amino acids, indicating the formation of small silver nanoparticles (AgNPs). Importantly, we found that individual biothiols (Hcy, Cys, and GSH) exert not only the anti-etching effect, but also the aggregating effect on AgNPRs, which can be modulated by simply tuning the pH conditions, and this consequently allows for the discriminative detection of each biothiol. Based on this simple and cost-effective strategy, we successfully determined the Hcy, Cys, and GSH in human serum with high sensitivity and selectivity within 10 min, demonstrating the diagnostic capability and potential in practical applications.